The impact of oil resources on the macroeconomic variables of the Algerian economy - Hidouchie, ََAchour; Aouil, Miloud (Milev Journal of Research and Studies, 2017)
The correlation between the achievement of development in Algeria and unstable oil resources due to the dominance of the hydrocarbon sector, which represents 60% of the general budget and about 40% as a contribution to the GDP turnover shows the fragility of the economy, as an economy of single production and resource, and given the scale of the financial resources of oil, especially in the period 2000-2014, and despite the improvement in performance of the Algerian economy in terms of achieving internal and external macroeconomic balances, but it was momentary and did not contribute to stimulate growth and create conditions for economic take-off. The improvement of these effects has required the allocation of large sums of money without creating productive sectors of value added. In the light of the instability, the question of the need to work to reduce the degree of dependence on the oil sector and to activate non-oil sources of income as an inevitable necessity to achieve development is asked.